To Identify the Prominent Factors of Shopping Mall Behaviour: A Factor Analysis Approach - Kaushal, Shailesh K.; Medhavi, Sanjay (Indian Journal of Marketing, 2011)
Retailing is gaining popularity day by day in India. Now, people in big cities have started buying high value products at shopping malls. The performance of the retail sector in the past few years has been outstanding, and we have witnessed a huge revamping exercise, significantly contributed by the growth of the organized retail chains. Rapid urbanization, exposure to large number of foreign brands and changing lifestyle and preferences have contributed to the growth of retailing in India. The quality of service perceived by the customers, irrespective of the brand is what ultimately results in a repeat visit of the customer. This study focuses on identifying the prominent factors affecting shopping mall buying behavior. A sample of 157 respondents was chosen on the basis of convenience sampling, and customer intercept survey was conducted in prominent shopping malls. A structured questionnaire on five point rating (Likert scale) was administered by way of personal interview. For the purpose of the analysis, statistical tools like Factor Analysis, Cronbach’s Alpha and Principal Component Analysis have been used. Twenty four factors affecting shopping mall consumer behaviour were identified. The three most prominent factors are quality, time saving and price.